Effect of P fertilization on the growth of Alnus acuminata plantations at Andisols of the Virilla river watershed, Costa Rica - Segura, Manuel (2005)
This study evaluated the effect of applying 0, 61, 122, 183 and 244 g P2O5 tree-1 to alder trees growing in Typic Udivitrands (Landelina y Vista de Mar) and Entic Udivitrands (Matinilla). It was found that available contents of P increase and content of amorphous Al and Fe and of the pH in NaF decreased in the soils of the 3 plantations. The addition of increasing levels of P to the soil did not alter the foliar concentration of any element significantly. However, with the addition of 61 g P2O5 tree-1 a slight increase was found in the foliar concentration of K in the plantation of Matinilla, and in the content of foliar B in the plantation of Landelina. The addition of P did not cause any difference in the trees’ diameter, height or volume in any of the places during the course of the trial (2 years). Nevertheless, when calculating the relative increase of growth parameters, the treatment of 61 g of P2O5 tree-1 showed the highest growth rate (tree height) in the 3 plantations. The differences in diameter, height and volume between ages were evident from the beginning of the experiment and remained constant during the experiment. In the 3.6 year old plantation the Current Annual Increment for the analyzed variables is higher than the one found in older plantations, in which it diminishes. The Mean Annual Increment reaches a maximum at 7.5 year of age and then tends to decrease.